Pengaruh Aspek Psikologis Terhadap Proses Persalinan Dan Pengaruhnya Terhadap Bayi - Siti Badria Asikin (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
The labor process is influenced not only by physiological factors but also by the mother's psychological state. Psychological factors such as anxiety, stress, and fear can affect the progress of labor and the condition of the newborn. This study aims to analyze the influence of maternal psychological aspects on the labor process and its impact on the baby's condition. The study used an analytical design with a cross-sectional approach. The study sample consisted of 70 mothers in labor, selected using a purposive sampling technique. Data were collected through a questionnaire on maternal anxiety levels and observations of the labor process and the baby's condition after birth. Data were analyzed using the chi-square test and logistic regression. The results showed that mothers with high levels of anxiety had a greater risk of prolonged labor and babies with lower Apgar scores (p < 0.05). It was concluded that maternal psychological conditions significantly influence the labor process and the condition of the newborn.